Percutaneous Subclavian Artery Covered Stent Placement Following Inadvertent Subclavian Arterial Cannulation - Cinosh Mathew1 , R Calton2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Inadvertent subclavian artery canulation although rare is a life threatening complication of central venouscanulation. Its prompt recognition and management by stent placement, thrombin injection, Angio seal orgel foam embolization is essential to minimize fatal complications. We describe a case report of subclavianarterial canulation which was recognized and managed percutaneously by covered stent placement withoutcomplications.